The golden age of murder : the mystery of the writers who invented the modern detective story - Edwards, Martin, 1955- (London : HarperCollinsPublishers, 2015)
"A real-life detective story, investigating how Agatha Christie and colleagues in a mysterious literary club transformed crime fiction, writing books casting new light on unsolved murders whilst hiding clues to their authors' darkest secrets."--Publisher's description.
Part one: the unusual suspects. The ritual in the dark ; A bitter sin ; Conversations about a hanged woman ; A Bolshevik soul in a Fabian muzzle ; Wearing their criminological spurs ; The art of self-tormenting -- Part two: the rules of the game. Setting a good example to the Mafia ; The Fungus-story and the meaning of life ; Wistful plans for killing off wives ; The least likely person ; The best advertisement in the world -- Part three: looking to escape. "Human life's the cheapest thing there is" ; Echoes of war ; Murder, transvestism and suicide during a trapeze act ; A severed head in a fish-bag ; "Have you hear of sexual perversions?" ; Clearing up the mess ; What it means to be stuck for money ; Neglecting Demosthenes in favour of Freud -- Part four: taking on the police. Playing games with Scotland Yard ; Why was the shift put in the boiler-hole? ; Trent's very last case ; A coffin entombed in a crypt of granite -- Part five: justifying murder. Knives engraved with "Blood and honour" ; Touching with a fingertip the fringe of great events ; Collecting murderers ; No judge or jury but my own conscience -- Part six: the end game. Playing the grandest game in the world ; The work of a pestilential creature ; Frank to the point of indecency ; Shocked by the brethren -- Part seven: unravelling the mysteries. Murder goes on forever.
Includes facsimile reproductions of the 1932 Constitution and Rules of the Detection Club (pages 441-447).
Includes bibliographical references (pages 449-457) and indexes.
Keywords: Detective and mystery stories, English -- History and criticism; Detective and mystery stories, English -- Bio-bibliography.; English fiction -- 20th century -- Bio-bibliography.; Novelists, English -- Biography; Murder in literature; Detection Club